Penerapan Introduction, Situation, Background, Assessment and Recommendation (ISBAR) untuk komunikasi efektif antara perawat dan dokter di Rumah Sakit Umum Daerah Cibabat Kota Cimahi - Asep Badrujamaludin; Tria Firza Kumala (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
ISBAR and effective communication between nurses and doctors Background: The communication errors the main cause of events reported to the United States Joint Commission between 1995 to 2006 of 25000-30000 preventable incidents that cause permanent disability. 11% of these adverse events are due to 6% different communication problems and also because inadequate level of skills. In Indonesia, data on unexpected-events (UEs)) let alone the event of near‐miss events (NMEs) is still scarce, but on the other hand there is an increase in accusations of